Tuḥfat al-azhār wa-zulāl al-anhār. Volume 1 : Fī nasab abnāʾ al-aʾimma al-aṭhār ʿalayhim ṣalawāt al-malik al-ghaffār - al-Jubūrī, Kāmil Salmān, (Miras Maktoob, ISBN: 9789004365452., 2019)
In traditional societies, ancestry is an important organising principle, often determining the lives of individuals or groups from the moment that they are born. In the Arab world, nasab (pl. ansāb ) or lineage was and to some extent still is, a major factor in the distribution of wordly and religious power, while administrative positions, trades, crafts and certain offices in the world of scholarship, too, often devolved along hereditary lines. Among the Shīʿa, where blood ties with the family of the Prophet through ʿAlī and his descendants are highly regarded and a source of authority and social standing, we find a number of ansāb works that focus exclusively on the genealogy of the twelve imams. Born into a Shīʿite family of ansāb scholars in 11th/17th-century Medina, the author of the present work travelled extensively in the Shīʿa world in his search for information. The result is a voluminous work, rich in material, genealogical and historic. 3 vols. & supplement al-Rawḍ al-miʿṭār fī tashjīr Tuḥfat al-azhār ; volume 1.